Production of ergothioneine by Methylobacterium species - Alamgir, Kabir M.; Masuda, Sachiko; Fujitani, Yoshiko; Fukuda, Fumio; Tani, Akio (Frontiers in Microbiology, 2015)
Metabolomic analysis revealed that Methylobacterium cells accumulate a large amount of ergothioneine (EGT), which is a sulfur-containing, non-proteinogenic, antioxidative amino acid derived from histidine. EGT biosynthesis and its role in methylotrophy and physiology for plant surface-symbiotic Methylobacterium species were investigated in this study. Almost all Methylobacterium type strains can synthesize EGT. We selected one of the most productive strains (M. aquaticum strain 22A isolated from a moss), and investigated the feasibility of fermentative EGT production through optimization of the culture condition. Methanol as a carbon source served as the best substrate for production. The productivity reached up to 1000 µg/100 ml culture (1200 µg/g wet weight cells, 6.3 mg/g dry weight) in 38 days. Next, we identified the genes (egtBD) responsible for EGT synthesis, and generated a deletion mutant defective in EGT production. Compared to the wild type, the mutant showed better growth on methanol and on the plant surface as well as severe susceptibility to heat treatment and irradiation of ultraviolet (UV) and sunlight. These results suggested that EGT is not involved in methylotrophy, but is involved in their phyllospheric lifestyle fitness of the genus in natural conditions.